Transnational economic order and national economic institutions: comparative capitalism meets international political economy - Andreas Nölke (Max Planck Institute for the Study of Societies, 2011)
Even after two decades of research on globalization, we still face open questions about the interplay between national capitalist nstitutions and transnational economic governance. How does embeddedness into transnational institutions influence national capitalist orders? How do national capitalist patterns influence transnational economic governance? The central suggestion of this paper is that the traditional divide between Comparative and International Political Economy has to be overcome in order to address these questions in a more thorough way. More specifically, it calls for combining Comparative Capitalism with institutionalist approaches within International Political Economy. The paper illustrates the mutually complementary character of both perspectives by looking at selected empirical examples. – – Auch nach zwei Dekaden der Globalisierungsforschung sind viele Fragen über die Wechselwirkung zwischen nationalen kapitalistischen Institutionen und transnationalen Wirtschaftsordnungen noch ungelöst. Wie beeinflusst die Einbettung in ransnationale Institutionen nationale Ausprägungen des Kapitalismus? Wie formen Muster des Kapitalismus auf nationaler Ebene die transnationale Wirtschaftsordnung? Das vorliegende Papier argumentiert, dass die traditionelle Trennung zwischen Vergleichender und Internationalerm Politischer Ökonomie (IPÖ) überwunden werden muss, um diese Fragen gründlicher bearbeiten zu können. Es wird insbesondere vorgeschlagen, transnationalinstitutionalistische IPÖ-Perspektiven mit dem Theorieprogramm der Vergleichenden Kapitalismusforschung zu verknüpfen. Das Papier demonstriert den komplementären Charakter der beiden Perspektiven an ausgewählten empirischen Beispielen.
Keywords: 300